Mineral Zeolite: Penyelamat Tanah, Air, dan Udara - H. Zulkarnain Muin (Jurnal Zeolit Indonesia, 2005)
God has given us rain / water as a mercy gift. Why, we are human being make it become a disaster? Why our efforts to overcome floods, pollutions until now, did not give good results yet? Because, the most precious gift has been given by God, free! And often, we can not appreciate something got free. That